Clinical evaluation of a newly designed orthodontic tooth brush - A clinical study - C S Saimbi; Jha Thulika; A K Mehrotra; Kaushal Shalini (Wolters Kluwer Medknow Publications, 2009)
In this study, a clinical trial was conducted with a newly designed orthodontic tooth brush, on ten subjects having fixed orthodontic appliances. In this newly designed tooth brush, the bristles of anterior portion of the head of the tooth brush are elongated and tapered towards the tip of the bristles and rest of the bristles are shorter than the anterior bristles. The inner bristles are further shorter than outer bristles row, providing a groove in the center of the brush. This groove is designed to engage the brackets. The elevated anterior bristles portion of the brush gets engaged in interproximal areas and cleans these areas. In this study, the newly designed orthodontic tooth brush is compared with an ordinary tooth brush. Results of this study show that the newly designed orthodontic tooth brush is superior in its cleaning efficiency as compared to the ordinary tooth brush. The results show that plaque removing capacity of orthodontic tooth brush is nearly 95-99%.